PENGARUH MATA KULIAH EDU-ENTERPRENEURSHIP TERHADAP MOTIVASI BERWIRAUSAHA MAHASISWA TADRIS IPA IAIN PAREPARE - Muhammad Ansar Apriansyah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
This study aims to analyze the effect of the Edu- Entrepreneurship course on student entrepreneurship motivation at IAIN Parepare. This study uses a quantitative research approach with an explanatory format to collect data on the effect of the Edu-Entrepreneurship course on student entrepreneurship motivation. The sample of this research is active students of IAIN Parepare who have taken the Edu- Entrepreneurship course. The data collected will be analyzed using statistical techniques to identify the relationship between the Edu-Entrepreneurship course and student entrepreneurship motivation. The results of the study showed that 71% of respondents said that the Edu-entrepreneurship course had an effect on increasing entrepreneurial motivation.